2022
DOI: 10.3390/v14102292
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-Associated COVID-19 across Five Pandemic Waves: Prediction Models and Genomic Analyses

Abstract: Background: Healthcare-associated SARS-CoV-2 infections need to be explored further. Our study is an analysis of hospital-acquired infections (HAIs) and ambulatory healthcare workers (aHCWs) with SARS-CoV-2 across the pandemic in a Belgian university hospital. Methods: We compared HAIs with community-associated infections (CAIs) to identify the factors associated with having an HAI. We then performed a genomic cluster analysis of HAIs and aHCWs. We used this alongside the European Centre for Disease Control (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Although sequencing capacity increased with time in our centre, we chose not to use individual variant identification, as this would have led to excessive missing data. We are confident that the Belgian national surveillance data reflects our catchment area’s epidemiology, as shown in another project published by our group recently [ 29 ]. We were also reassured to read a recent paper by Meurisse et al [ 11 ], who found that exposure ascertainment based on time periods leads to the most precise results when studying severity per variant wave.…”
Section: Discussionmentioning
confidence: 59%
“…Although sequencing capacity increased with time in our centre, we chose not to use individual variant identification, as this would have led to excessive missing data. We are confident that the Belgian national surveillance data reflects our catchment area’s epidemiology, as shown in another project published by our group recently [ 29 ]. We were also reassured to read a recent paper by Meurisse et al [ 11 ], who found that exposure ascertainment based on time periods leads to the most precise results when studying severity per variant wave.…”
Section: Discussionmentioning
confidence: 59%